Understanding the role of DHN melanin in Cryomyces antarcticus - Catanzaro, Ilaria (2023)
Cryomyces antarcticus – a cryptoendolithic black fungus endemic to Antarctica – is taxonomically classified in phylum Ascomycota, class Dothideomycetes incertae sedis. C. antarcticus has shown high capability to survive extreme environmental conditions like those found in space (ionizing radiation, vacuum, microgravity), thus fueling fundamental astrobiological questions like “searching for life beyond Earth” (Onofri et al. 2020, Extremophiles Astrobiol Model). Its extraordinary resilience has been attributed to the presence of thick, highly melanized cell walls, which may contain both DHN and DOPA melanins (Pacelli et al. 2020, Appl Microbiol Biotechnol). To better understand the contribution of DHN melanin to the overall resilience of C. antarcticus, we initially adopted chemicals e.g., tricyclazole to inhibit the DHN melanin synthetic pathway; however, these studies gave inconclusive results. Eventually, we decided to generate melanin-deficient mutants by genetic engineering. Using the genetic toolkit developed for the black fungus Knufia petricola (Voigt et al. 2020, Sci Rep; Erdmann et al. 2022, Front Fungal Biol), we designed a strategy for mutating the key enzyme (polyketide synthase)-encoding gene capks1 by transient delivery of Cas9 and capks1-specific sgRNA from AMA-containing plasmids and PCR-generated donor DNA i.e., resistance cassettes flanked by ~75-bp-long sequences homologous to capks1. For this, the melanin-PKS encoding ortholog was identified in the C. antarcticus CBS 116301 genome (mycocosm.jgi.doe.gov) and used to design primers for re-sequencing of the capks1 locus in the strain CCFEE 515. Transformation of C. antarcticus is challenging because of its very slow growth; we expect that 4-6 months are needed from obtaining enough biomass for cell wall lysis until transferring putatively resistant transformants for genotyping. Important parameters were evaluated: protoplasts can be generated, and they survive the transformation procedure, and suitable concentrations of selective agents have ...